Political Communication Strategy in Building Party Image Ahead of the 2024 Legislative Election (Case study of DPD Golkar Party DKI Jakarta) - Michelle Anastasya Supriyadi; Nurdin Nurdin (Jurnal Ilmiah Ilmu Administrasi Publik, 2024)
This research aims to analyze the political communication strategy of the DKI Jakarta Golkar DPD in rebuilding the party's positive image ahead of the 2024 legislative elections. The research method used is qualitative with a descriptive approach. Secretary of the DKI Jakarta Golkar DPD, Chair of the DKI Jakarta DPRD, Golkar Faction, Deputy Chair for Organizational Affairs and Membership of DPD Golkar, Academics and Community Figures. The data collection techniques used in this research come from primary and secondary data using observation, interviews, and documentation. Meanwhile, the data analysis techniques used were data reduction, data presentation, and the withdrawal of political communication strategies using a political marketing approach carried out by DPD Golkar DKI Jakarta, which was successful in rebuilding the political image that had fallen since the corruption case involving the chairman of the DPD. The implication of the success of this political image is an increase in votes and seats in the results of the 2024 Legislative Election.